Financial Literacy on Impulsive Buying Behavior in Y Generation - Nur Aini Anisa; Syamsul Arifin; Lis Setyowati; Nur Hidayah; Aisyah Darti Megasari (Quantitative Economics and Management Studies, 2020)
Impulse buying is a phenomenon that can occur in all generations but more done by the generation that undergoes a change that is the age of adolescents who step on the early adulthood of the Y generation who actually do not have the financial ability to meet their needs. This study aims to analyze the influence of financial literacy on the impulsive buying behavior of online products in Y generation. This research is a descriptive research type, with a quantitative approach. The population of 733 students. The sampling technique used in this research is nonprobability sampling by using purposive sampling type with sample of 142 students. The subject of this research is the students of university. Data collection technique using questionnaire. Data were analyzed using linear regression analysis. The result of data analysis shows that there is influence of financial literacy on impulse buying behavior of online product in Y generation. It means the higher the student's financial literacy, the lower the impulse buying behavior. Conversely, the lower the student's financial literacy, the higher the impulse buying behavior. Data were analyzed using linear regression analysis. The result of data analysis shows that financial literacy has negative effect, but significant to impulsive buying behavior of online product in Y generation. It means The higher student's financial literacy, the lower impulse buying behavior. Conversely, the lower student's financial literacy, the higher impulse buying behavior.